Impact of Platinum Loading on Performance and Degradation of Polymer Electrolyte Fuel Cell Electrodes Studied in a Rainbow Stack1. Issue 3 (25th October 2017) - Gazdzicki, P.; Mitzel, J.; Dreizler, A. M.; Schulze, M.; Friedrich, K. A.
Abstract: The paper focuses on the investigation of durability and performance of a low temperature polymer electrolyte membrane fuel cell (PEMFC) stack as a function of Pt loading in automotive test conditions. Major motivations are problems related to the need to reduce the amount of Pt in membrane electrode assemblies (MEAs) in order to make PEMFC more competitive. The particular challenge is to maintain sufficiently high performance and long‐term durability. The study shows that for cathode Pt loadings below 0.2 mg cm −2 and for current densities exceeding 1 A cm −2 a sudden drop of performance is observed. The same threshold value is found for the increase of irreversible voltage losses which lead to an intense reduction of PEMFC durability for cathodic loadings below 0.2 mg cm −2 . Another durability issue at cathodic Pt loadings < 0.4 mg cm −2 is the acceleration of reversible degradation, which leads to a strong voltage drop during continues fuel cell operation (i.e., without a recovery interruption).